Electrical properties of C/C and C/C-SiC ceramic fibre composites - Singh S.; Srivastava V.K. (My University, 2025)
The electrical properties of carbon/carbon (C/C) and carbon/carbon-silicon carbide (C/C-SiC) ceramic composites were measured. The results show that the capacitance decreases rapidly with an increase in frequency and it becomes constant above a frequency of 500 kHz, whereas the dissipation factor increases with increasing frequency. C/C-SiC composites give higher value than C/C composites due to the presence of microcracks. © 2010 Elsevier Ltd and Techna Group S.r.l.